2014
DOI: 10.2478/s11756-014-0375-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid and high frequency Agrobacterium rhizogenes mediated transformation protocol for Ocimum tenuiflorum

Abstract: A rapid and efficient Agrobacterium rhizogenes mediated transformation system for Ocimum tenuiflorum L., a traditional Indian medicinal plant that occurs in red and green forma, was developed. The plant is a repertoire of several pharmaceutically and nutraceutically important metabolites. Three different types of explants i.e. leaves, hypocotyls and excised shoots, obtained from shoot cultures of in vitro germinated red and green forma plants were transformed using Agrobacterium rhizogenes strain ATCC 15834. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Mostly, young leaves of in vitro-germinated seedlings were used to infect with A. rhizogenes. Studies also reported the use of stems (Bais et al, 2002;Marzouk, 2009), as well as hypocotyl and cotyledon (Vyas and Mukhopadhyay, 2014;Srivastava et al, 2016b), for transformation purposes. Therefore, leaves from green variety of O. sanctum and Subja cultivar of O. basilicum are better to achieve more clones and higher biomass on MS media after treatment of cefotaxime or claforan.…”
Section: Media and Explant Used For Transformationmentioning
confidence: 99%
See 4 more Smart Citations
“…Mostly, young leaves of in vitro-germinated seedlings were used to infect with A. rhizogenes. Studies also reported the use of stems (Bais et al, 2002;Marzouk, 2009), as well as hypocotyl and cotyledon (Vyas and Mukhopadhyay, 2014;Srivastava et al, 2016b), for transformation purposes. Therefore, leaves from green variety of O. sanctum and Subja cultivar of O. basilicum are better to achieve more clones and higher biomass on MS media after treatment of cefotaxime or claforan.…”
Section: Media and Explant Used For Transformationmentioning
confidence: 99%
“…Strain ATCC 15834 ( Tada et al, 1996 ; Bais et al, 2002 ; Vyas and Mukhopadhyay, 2014 ) and strain LBA 9402 ( Skorupinska-Tudek et al, 2007 ; Marzouk, 2009 ) of A. rhizogenes were preferred during most studies to infect O. sanctum and O. basilicum . Other strains of A. rhizogenes used were MAFF 03-01724 ( Tada et al, 1996 ), A4, Arqua1-pTSC5, 8196, and 11325 ( Srivastava et al, 2016b , c ).…”
Section: Hairy Root Culture : Agrobacterium Rhizogenes -Mediated Transformationmentioning
confidence: 99%
See 3 more Smart Citations